2018
DOI: 10.1121/1.5049802
|View full text |Cite
|
Sign up to set email alerts
|

Validating automated click detector dolphin detection rates and investigating factors affecting performance

Abstract: Passive acoustic monitoring (PAM) is a widely used technique for studying the distribution and habitat use of cetaceans. The C-POD, an acoustic sensor with an onboard automated click detector, has been deployed in diverse acoustic environments, but studies verifying its offshore detection rates and factors affecting detection probability are scarce. To empirically evaluate the performance of C-PODs in detecting bottlenose dolphins (), C-PODs were deployed alongside archival acoustic recorders 12-30 km offshore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…, Garrod et al. ). These devices continuously monitor the frequency range 20–160 kHz, although they do not record the complete soundstream (details available online ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Garrod et al. ). These devices continuously monitor the frequency range 20–160 kHz, although they do not record the complete soundstream (details available online ) .…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected using C-PODs (Chelonia, Cornwall, UK), which detect and log odontocete echolocation clicks. The C-PODs were moored approximately 3 m from the seabed attached to a 45-kg anchor weight and were retrieved and redeployed approximately every 3 months (Wingfield et al 2017, Garrod et al 2018). These devices continuously monitor the frequency range 20-160 kHz, although they do not record the complete soundstream (details available online).…”
Section: Acoustic Data Collectionmentioning
confidence: 99%
“…While no dolphins were detected during the 2 loudest days of our study period (average sound levels of up to 126 dB re 1 µPa rms in 2015), on the loudest days in 2016 and 2017, dolphin presence and foraging were detected despite elevated ambient sound levels during the storm. A previous study in this region showed that the C-POD's ability to detect dolphins (based on click trains between 20 and 160 kHz) was not significantly affected by broadband (2 Hz-24 kHz, up to 130 dB re 1 µPa rms) ambient sound levels 53 . Storm noise, which has most of its energy in lower frequencies, did not appear to greatly reduce detections by the C-POD.…”
Section: Discussionmentioning
confidence: 85%
“…While dolphins were detected throughout our study period, including on days with high ambient sound levels (up to 123 dB re 1 µPa rms), elevated ambient sound levels during the storms likely masked dolphin clicks 50,51 or decreased the detection range of the C-POD 52 . The C-POD's KERNO classifier is also a conservative classifier of dolphin clicks 53 . While no dolphins were detected during the 2 loudest days of our study period (average sound levels of up to 126 dB re 1 µPa rms in 2015), on the loudest days in 2016 and 2017, dolphin presence and foraging were detected despite elevated ambient sound levels during the storm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation